Thrombophilia-Associated Factors in Patients with Spontaneous Osteonecrosis of the Knee. (January 2019) - Marom, Niv; Koch, Jonathan EJ.; Beer, Yiftah; Ellis, Martin; Ganot, Gil; Nyska, Meir; Maoz, Guy; Hetsroni, Iftach
Objective: To test whether patients with spontaneous osteonecrosis of the knee (SONK) are characterized by abnormal levels of thrombophilia-associated factors. Design: Twenty-five patients with SONK were recruited. Inclusion criteria were (1) age >40 years, (2) acute onset knee pain not precipitated by trauma, and (3) MRI findings consistent with SONK. Exclusion criteria were (1) history of cancer and chemotherapy and (2) factors associated with secondary osteonecrosis. Blood tests included 13 thrombophilia-associated factors that were either heritable mutations or acquired factors. Descriptive statistics included medians, ranges, means, and standard deviations. Mann-Whitney test was used to compare thrombophilia-associated factor levels between the sexes. Spearman's rank test was used to test correlations between smoking status and each thrombophilia-associated factor. Level of significance was set at 0.05. Results: Median patient age was 62 years (range, 44-77 years). There were 16 (64%) men. Thirteen (52%) patients had thrombophilia-associated factor abnormalities of which 9 were elevated fibrinogen but this was less than 1 standard deviation above norm threshold. Other findings were 3 patients with marginally decreased antithrombin below norm threshold, low protein S Ag in only 1 patient, and factor V Leiden mutation heterozygosity in 2 patients, which was not higher than normal population prevalence. Thrombophilia-associated factors neither differed between sexes ( P = nonsignificant) nor correlated with smoking status ( P = nonsignificant). Conclusion: Thrombophilia-associated factor abnormalities in patients with SONK were minimal. Therefore, clinical workup and treatment strategy in this disease should focus on addressing alternative etiologies leading to abnormal subchondral bone metabolism with focal osteopenia.